2017
DOI: 10.1001/jamaneurol.2017.2459
|View full text |Cite
|
Sign up to set email alerts
|

Association of an Electroencephalography-Based Risk Score With Seizure Probability in Hospitalized Patients

Abstract: IMPORTANCE Continuous electroencephalography (EEG) use in critically ill patients is expanding. There is no validated method to combine risk factors and guide clinicians in assessing seizure risk.OBJECTIVE To use seizure risk factors from EEG and clinical history to create a simple scoring system associated with the probability of seizures in patients with acute illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
119
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(140 citation statements)
references
References 24 publications
8
119
0
2
Order By: Relevance
“…A seizure prediction model designed in neonates incorporating EEG background features with clinical data improved ES prediction over a model employing clinical variables alone . Our finding that the presence of epileptiform discharges predicted ES is also supported by other studies in critically ill children and adults . Overall, the consistency between the predictors of ES identified in this study and those identified by other groups suggest validity and generalizability of this model.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A seizure prediction model designed in neonates incorporating EEG background features with clinical data improved ES prediction over a model employing clinical variables alone . Our finding that the presence of epileptiform discharges predicted ES is also supported by other studies in critically ill children and adults . Overall, the consistency between the predictors of ES identified in this study and those identified by other groups suggest validity and generalizability of this model.…”
Section: Discussionsupporting
confidence: 85%
“…47 Our finding that the presence of epileptiform discharges predicted ES is also supported by other studies in critically ill children 2,5,6,12,17 and adults. 46,48,49 Overall, the consistency between the predictors of ES identified in this study and those identified by other groups suggest validity and generalizability of this model.…”
Section: Discussionsupporting
confidence: 74%
“…сание ЭЭГ, увеличив уровень межэкспертного согласия и провести ряд кооперативных исследований, выявивших клиническую значимость отдельных паттернов [16,17].…”
Section: рис 1 схема протокола ээг у пациента с угнетением уровня бunclassified
“…По шкале 2HELP2B, оценивающей риск развития приступа по данным ЭЭГ, кратковременные иктальные ритмичные разряды соответствуют 2 баллам; ЛПР или ЛРДА или БиПР -2; эпилептический приступ до начала регистрации ЭЭГ -1; спорадические ЭР -1; частота графоэлементов в РПП выше 2 Гц -1; наличие любого модификатора «+» -1 балл. Риск приступа для 0 баллов составляет 5%, для 1 балла -12%, 2 баллов -27%, 3 баллов -50%, 4 баллов -73%, 5 баллов -88%, 6 и 7 баллов -95% [35]. Второй способ -использование шкалы ГПР, которая включает эпилепсию в анамнезе (1 балл), фокальные изменения на ЭЭГ (2 балла), отсутствие трехфазной морфологии ПР (3 балла) [36].…”
Section: прогнозирование судорожного и бессудорожного эпилептическогоunclassified
“…2 Depending on various waveform characteristics, acute electrographic seizures are noted in 12%-58% of patients with PPs on cEEG. 2 Above findings along with a recently proposed cEEG-based risk scoring model for seizures during hospitalization 4 have vastly improved our understanding of acute impact of PPs. However, their impact on long-term, posthospitalization clinical outcomes is largely unknown.…”
mentioning
confidence: 97%